Copper foil with resin layer attached and laminate using the same
Patent Information
- Application Number
- KR1020237005098
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-08-13
- Filing Date
- 2021-08-07
- Publication Date
- 2026-09-11
- Estimated Expiration
- 2041-08-07
Smart Images

Figure 112023016425850-PCT00019_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a copper foil with a resin layer attached and a laminate using the same. More specifically, the present invention relates to a copper foil with a resin layer attached that is useful for a printed circuit board or a substrate for mounting semiconductor devices, and a laminate using the same. Background Technology
[0002] Recently, printed circuit boards or substrates for mounting semiconductor devices, which are widely used in electronic devices, communication devices, and personal computers (PCs), have seen advancements in high density, high integration, and thinning. Accordingly, as a manufacturing method for printed circuit boards or substrates for mounting semiconductor devices, the build-up method, in which a conductor layer with a circuit formed thereon and an insulating layer (interlayer insulating layer) are alternately stacked, is widely used, and the semi-additive method, which can form fine patterns, is commonly used for forming wiring patterns.
[0003] As an insulating layer used in such printed circuit boards, it is known that a resin composition layer is multilayered (see, for example, Patent Document 1). Patent Document 1 relates to a resin insulating sheet in which the etching amount of each layer is controlled to improve the performance of the multilayered insulating layer. Prior art literature
[0004] Patent Document 1: Japanese Patent Publication No. 2017-50561 The problem to be solved
[0005] However, the resin insulating sheet described in Patent Document 1 requires that the total thickness of each layer be at least 12 μm. For this reason, there has been a demand for the development of a technology that can satisfy requirements such as insulation, plating adhesion, and moisture absorption and heat resistance while making thinning (e.g., less than 10 μm) even more possible.
[0006] The present invention is made based on such problems and aims to provide a copper foil with a resin layer attached that has excellent insulation, plating adhesion, and moisture absorption and heat resistance, and a laminate using the same. means of solving the problem
[0007] The inventors have discovered that the above problem can be solved by adjusting the composition of the first resin layer and the surface roughness of the copper foil in a copper foil having a copper foil and a first resin layer laminated on the surface of the copper foil, and thus have completed the present invention.
[0008] That is, the present invention is as follows.
[0009] [1]
[0010] A copper foil having a copper foil and a first resin layer laminated on the surface of the copper foil, wherein the copper foil has a resin layer attached thereto,
[0011] The first resin layer comprises a polyphenylene ether compound (A), a polyimide resin (B), and a maleimide compound (C).
[0012] The 10-point average roughness Rz of the surface of the copper foil is 0.3㎛ or more and 10㎛ or less.
[0013] Copper foil with a resin layer attached, characterized by the following:
[0014] [2]
[0015] A copper foil with a resin layer attached as described in [1], wherein a second resin layer containing a thermosetting resin is formed on the first resin layer.
[0016] [3]
[0017] The ratio of the polyphenylene ether compound (A) in the first resin layer is 3 parts by mass or more and less than 20 parts by mass per 100 parts by mass of resin solid content, as described in [1], a copper foil with a resin layer attached.
[0018] [4]
[0019] The first resin layer described above is a copper foil with a resin layer attached as described in [1], which does not contain an inorganic filler or contains an inorganic filler in an amount of 35 volume% or less.
[0020] [5]
[0021] The above inorganic filler is a copper foil with a resin layer attached as described in [4], containing at least one selected from magnesium hydroxide, magnesium oxide, silica, molybdenum compound, alumina, aluminum nitride, glass, talc, titanium compound, and zirconium oxide.
[0022] [6]
[0023] Copper foil with a resin layer attached as described in [1], wherein the thickness of the first resin layer is 1.5㎛ or more and 5㎛ or less.
[0024] [7]
[0025] The second resin layer described above is a copper foil with a resin layer attached as described in [2], containing at least one selected from the group consisting of epoxy compounds, cyanate ester compounds, maleimide compounds, phenol compounds, polyphenylene ether compounds, benzoxazine compounds, organically modified silicone compounds, and compounds having polymerizable unsaturated groups.
[0026] [8]
[0027] The second resin layer described above is a copper foil with a resin layer attached as described in [2], which does not contain inorganic filler or contains inorganic filler in an amount of 36 volume% or less.
[0028] [9]
[0029] The above inorganic filler is a copper foil with a resin layer attached as described in [8], containing at least one selected from magnesium hydroxide, magnesium oxide, silica, molybdenum compound, alumina, aluminum nitride, glass, talc, titanium compound, and zirconium oxide.
[0030]
[10]
[0031] Copper foil with a resin layer attached as described in [2], wherein the thickness of the second resin layer is 1 μm or more and 15 μm or less.
[0032]
[11]
[0033] A laminate having a conductor layer and a build-up layer formed using a copper foil with a resin layer attached as described in [1]. Effects of the invention
[0034] According to the present invention, a copper foil with a resin layer attached having excellent insulation, plating adhesion, and moisture absorption and heat resistance, and a laminate using the same can be provided. Brief explanation of the drawing
[0035] FIG. 1 is a schematic diagram showing the configuration of a copper foil with a resin layer attached according to one embodiment of the present invention. FIG. 2 is a schematic diagram showing an example of a laminate according to one embodiment of the present invention. FIG. 3 is a schematic diagram showing an example of a multilayer coreless substrate according to one embodiment of the present invention. Specific details for implementing the invention
[0036] Below, forms for carrying out the present invention (hereinafter referred to as "the present embodiment") will be described in detail, but the present invention is not limited thereto and various modifications are possible within the scope of not departing from the gist thereof. In this specification, the laminate is formed such that each layer is bonded to each other, but the layers may be detachable from each other as needed.
[0037] In this embodiment, “resin solids” refers to the components excluding solvents and inorganic fillers in the first resin layer (12) or the second resin layer (13) unless otherwise specified, and “100 parts by mass of resin solids” refers to the total of the components excluding solvents and inorganic fillers in the first resin layer (12) or the second resin layer (13) being 100 parts by mass.
[0038] [Copper foil with resin layer attached]
[0039] FIG. 1 shows the configuration of a copper foil (10) with a resin layer attached according to one embodiment of the present invention. The copper foil (10) with a resin layer attached comprises a copper foil (11) and a first resin layer (12) laminated on the surface of the copper foil (11), and preferably has a second resin layer (13) further formed on the first resin layer (12).
[0040] This copper foil (10) with a resin layer attached is useful as a material for forming an insulating layer placed on, for example, a circuit pattern (conductor layer), and can be used as a material for forming an insulating layer of a printed circuit board or a substrate for mounting semiconductor devices used in the manufacture of, for example, electronic devices, communication devices, and PCs. For example, when manufacturing a printed circuit board, etc., the copper foil (10) with a resin layer attached is placed on a substrate on which a conductor layer, such as a circuit pattern, is formed, so that the second resin layer (13) and the conductor layer are in contact, and then the first resin layer (12) and the second resin layer (13) are cured by applying heat and pressure (pressing), thereby forming an insulating layer on the conductor layer.
[0041] The first resin layer (12) is a layer that maintains the distance between the copper foil (11) and the conductor layer even after press processing, such as when forming a laminate, in order to maintain insulation between the conductor layer and the copper foil (11). The second resin layer (13) is a layer containing a resin that has fluidity during press processing, and is a layer into which an uneven portion, such as a conductor layer of a circuit pattern, is inserted. Since the second resin layer (13) functions as an embedded layer, it is preferable that at least one of the constituent components and physical properties is different from that of the first resin layer (12). Although not specifically limited, examples of different forms in which the first resin layer (12) and the second resin layer (13) are different include cases where the resin types, etc., are different and the components are different, such as using a polyimide resin in the first resin layer (12) and an epoxy compound in the second resin layer (13); cases where the physical properties are different depending on the mixing ratio of the components included in each layer or the curing state (for example, by changing the coating conditions of each layer to completely cure the first resin layer (12) and make the second resin layer (13) semi-cured, etc.); and cases where these are combined.
[0042] [Copper foil]
[0043] The copper foil (11) may be any material used in ordinary printed circuit boards, such as electrolytic copper foil, rolled copper foil, and copper alloy film. The copper foil (11) may have known surface treatments such as matt treatment, corona treatment, nickel treatment, and cobalt treatment. As for the copper foil (11) in this embodiment, commercially available products may be used, such as “GHY5” (product name, 12㎛ thick copper foil) and “JXUT-Ⅰ” (product name, 1.5㎛ thick copper foil) from JX Nippon Mining & Metals Corporation, “MT-FL” (product name, 3㎛ thick copper foil), “3EC-VLP” (product name, 12㎛ thick copper foil), “3EC-Ⅲ” (product name, 12㎛ thick copper foil) and “3EC-M2S-VLP” (product name, 12㎛ thick copper foil) from Mitsui Mining & Smelting Co., Ltd., and “GTS-MP” (product name, 12㎛ thick copper foil) from Furukawa Electric Co., Ltd.
[0044] The 10-point average roughness Rz of the surface of the copper foil (11), that is, the 10-point average roughness Rz of the surface of the copper foil (11) on the side where the first resin layer (12) is formed, is preferably 0.3 μm or more and 10 μm or less. This is because plating adhesion can be improved by making it 0.3 μm or more. Also, if it is greater than 10 μm, it is not desirable because the thickness of the first resin layer (12) must be increased to ensure insulation. A more desirable range for the 10-point average roughness Rz of the surface of the copper foil (11) is, for example, 0.6 μm or more and 2.5 μm or less. In addition, it is preferable that the 10-point average roughness Rz of the surface of the copper foil (11) be smaller than the thickness of the first resin layer (12). This is to increase insulation. The 10-point average roughness Rz of the surface of the copper foil (11) can be measured using a commercially available shape measuring microscope (a laser microscope, for example, a product of KEYENCE CORPORATION, “VK-X1000” (product name)).
[0045] The thickness of the copper foil (11) is not particularly limited, but considering the surface treatment, a range of 1 μm to 18 μm is preferred, and a range of 2 μm to 15 μm is more preferred in order to suitably obtain a thin printed circuit board and a substrate for mounting semiconductor devices.
[0046] [First resin layer]
[0047] The first resin layer (12) comprises a polyphenylene ether compound (A), a polyimide resin (B), and a maleimide compound (C). Additionally, the first resin layer (12) may include at least one of other resin components, inorganic fillers, and other components as needed. The thickness of the first resin layer (12) is not particularly limited, but it is preferable that it be 5 μm or less from the perspective of thin film formation, and 1.5 μm or more when considering the securing of insulation properties. The thickness of the first resin layer (12) can be determined, for example, by making a sample for measurement by hardening the resin on a copper foil (10) with a resin layer attached, cutting it to show a vertical cross-section, polishing it, and observing the vertical cross-section under a microscope. For example, the measurement method is defined as the distance from the surface opposite to the copper foil (11) of the first resin layer (12) in a vertical direction to the interface with the copper foil (11), and the distance from the average position of the uneven interface between the first resin layer (12) and the copper foil (11) to the surface opposite to the copper foil (11) of the first resin layer (12) is defined as the thickness of the first resin layer (12). The first resin layer (12) may be in a semi-cured state (B-Stage) or a fully cured state (C-Stage). The first resin layer (12) may be formed by known means, such as coating, for example.
[0048] <Polyphenylene ether compound (A)>
[0049] The polyphenylene ether compound (A) according to the present embodiment is a compound represented by the general formula (1). By including the polyphenylene ether compound (A), insulation properties, plating adhesion, and moisture absorption and heat resistance can be improved. The polyphenylene ether compound (A) represented by the general formula (1) used in the present embodiment preferably has a number average molecular weight of 1,000 or more and 7,000 or less. By making the number average molecular weight 7,000 or less, compatibility between resins can be controlled. In addition, by making the number average molecular weight 1,000 or more, excellent insulation properties and moisture absorption and heat resistance inherent to the polyphenylene ether resin can be obtained. Among these, to obtain even better compatibility, insulation properties, and moisture absorption and heat resistance, it is preferable that the number average molecular weight of the polyphenylene ether compound (A) be 1,100 or more and 5,000 or less. More preferably, the number average molecular weight of the polyphenylene ether compound (A) is 4500 or less, and even more preferably, the number average molecular weight of the polyphenylene ether compound (A) is 3000 or less. The number average molecular weight is measured using gel permeation chromatography according to a prescribed method.
[0050]
[0051] (In general formula (1), X represents an aryl group (aromatic group), -(YO)n2- represents a polyphenylene ether portion, R1, R2, and R3 each independently represent a hydrogen atom, an alkyl group, an alkenyl group, or an alkynyl group, n2 represents an integer from 1 to 100, n1 represents an integer from 1 to 6, and n3 represents an integer from 1 to 4. Preferably, n1 is an integer from 1 to 4, more preferably n1 is 1 or 2, and ideally n1 is 1. Also, preferably n3 is an integer from 1 to 3, more preferably n3 is 1 or 2, and ideally n3 is 2.)
[0052] The polyphenylene ether compound (A) represented by general formula (1) preferably comprises a polymer of constituent units represented by the following general formula (2).
[0053]
[0054] (Among general formula (2), R 901 , R 902 , R 903 , R 904 Each represents an alkyl group, aryl group, halogen atom, or hydrogen atom having 6 or fewer carbon atoms independently.
[0055] The above polymer may further include at least one structural unit selected from the group consisting of structural units represented by general formula (3) and general formula (4).
[0056]
[0057] (Among general formula (3), R 905 , R 906 , R 907 , R 911 , R 912 Each represents an alkyl group or a phenyl group having 6 or fewer carbon atoms independently. R 908 , R 909 , R 910 Each represents independently a hydrogen atom, an alkyl group with 6 or fewer carbon atoms, or a phenyl group.
[0058]
[0059] (Among general formula (4), R 913 , R 914 , R 915 , R 916 , R 917 , R 918 , R 919 , R 920 Each represents independently a hydrogen atom, an alkyl group having 6 or fewer carbon atoms, or a phenyl group. -A- is a straight-chain, branched, or cyclic divalent hydrocarbon group having 20 or fewer carbon atoms.
[0060] In relation to general formula (1), it is preferable that the above general formulas (2), (3), and (4) are -(YO)- of general formula (1). -(YO)- has a repeating unit of n2 (1 to 100).
[0061] As the aryl group in X of the general formula (1), an aromatic hydrocarbon group may be used. Specifically, a group obtained by removing n3 hydrogen atoms from one type of ring structure selected from a benzene ring structure, a biphenyl structure, an indenyl ring structure, and a naphthalene ring structure (e.g., a phenyl group, a biphenyl group, an indenyl group, and a naphthyl group) may be used, and preferably, a biphenyl group may be used. Here, the aryl group may include a diphenyl ether group in which the aryl group is bonded to an oxygen atom, a benzophenone group bonded to a carbonyl group, a 2,2-diphenylpropane group bonded to an alkylene group, etc. Additionally, the aryl group may be substituted by a general substituent such as an alkyl group (preferably an alkyl group having 1 to 6 carbon atoms, particularly a methyl group), an alkenyl group, an alkynyl group, or a halogen atom. However, since the above "aryl group" substitutes the polyphenylene ether portion with an oxygen atom in between, the limit on the number of substituents generally depends on the number of polyphenylene ether portions.
[0062] As for the polyphenylene ether compound (A), it is particularly preferable to include a polyphenylene ether represented by the structure of the following general formula (5).
[0063]
[0064] (In general formula (5), X is an aryl group (aromatic group), -(YO)n2- represents a polyphenylene ether portion, and n2 represents an integer from 1 to 100.)
[0065] -(YO)n2- and n2 have the same meaning as in general formula (1). n2 may include multiple types of different compounds.
[0066] In general formulas (1) and (5), X is preferably general formula (6), general formula (7), or general formula (8), and in general formulas (1) and (5), -(YO)n2- is preferably a structure in which general formula (9) or general formula (10) is arranged, or a structure in which general formula (9) and general formula (10) are randomly arranged.
[0067]
[0068]
[0069] (Among general formula (7), R 921 , R 922 , R 923 , R 924 Each represents an independent hydrogen atom or a methyl group. -B- is a straight-chain, branched, or cyclic divalent hydrocarbon group with 20 or fewer carbon atoms.
[0070]
[0071] (In general formula (8), -B- is a straight-chain, branched, or cyclic divalent hydrocarbon group with 20 or fewer carbon atoms)
[0072]
[0073]
[0074] The method for manufacturing a modified polyphenylene ether having a structure represented by the general formula (5) is not particularly limited, and, for example, can be manufactured by converting the terminal phenolic hydroxyl group of a difunctional phenylene ether oligomer obtained by oxidative coupling of a difunctional phenol compound and a monofunctional phenol compound into vinylbenzyl ether.
[0075] In addition, commercially available modified polyphenylene ethers can be used, for example, OPE-2St1200 and OPE-2St2200 products from Mitsubishi Gas Chemical Company, Inc. can be suitably used.
[0076] In the present embodiment, the proportion of the polyphenylene ether compound (A) is preferably 1 part by mass or more and 3 parts by mass or more with respect to 100 parts by mass of the resin solid content of the first resin layer (12). In addition, the upper limit of the above content is preferably less than 20 parts by mass. By maintaining this range, interlayer adhesion, plating adhesion, and moisture absorption and heat resistance can be effectively improved. The first resin layer (12) may contain only one type of polyphenylene ether compound (A) or may contain two or more types. When two or more types are included, the total amount is preferably within the above range.
[0077] <Polyimide resin (B)>
[0078] As for the polyimide resin (B), a commercially available product may be appropriately selected and used, for example, a solvent-soluble polyimide resin synthesized by the manufacturing method described in Japanese Patent Publication No. 2005-15629 may be used. Specifically, the solvent-soluble polyimide resin can be obtained by polycondensing one or more selected from an aliphatic tetracarboxylic acid dianhydride represented by the following formula (11), an aliphatic tetracarboxylic acid represented by the following formula (12), and a derivative of the aliphatic tetracarboxylic acid, and one or more diamine compounds in a solvent in the presence of a tertiary amine compound.
[0079]
[0080] (In the formula, R is a tetravalent aliphatic hydrocarbon group having 4 to 16 carbon atoms)
[0081]
[0082] (In the formula, R is a tetravalent aliphatic hydrocarbon group having 4 to 16 carbon atoms, and Y1 to Y4 are independently hydrogen or a hydrocarbon group having 1 to 8 carbon atoms)
[0083] In the above manufacturing method, nearly equimolar amounts of aliphatic tetracarboxylic acids and a diamine compound can be heated in a solvent in the presence of a tertiary amine compound to perform polycondensation. Additionally, the reaction molar ratio of the aliphatic tetracarboxylic acids and the diamine compound is preferably in the range of 95 to 105 mol% for each of the two.
[0084] In the manufacture of general polyimide resins, tetracarboxylic acid dianhydrides are usually used as tetracarboxylic acids, but in the above manufacturing method, in addition to aliphatic tetracarboxylic acid dianhydrides, practical polyimide resins can be manufactured by using aliphatic tetracarboxylic acids or esters of aliphatic tetracarboxylic acids and alcohols. If aliphatic tetracarboxylic acids can be used as they are, it is advantageous in terms of production facilities and costs.
[0085] In addition, examples of aliphatic tetracarboxylic acid dianhydrides represented by formula (11) include 1,2,3,4-cyclobutanetetracarboxylic acid dianhydride, 1,2,4,5-cyclopentanetetracarboxylic acid dianhydride, 1,2,4,5-cyclohexanetetracarboxylic acid dianhydride, bicyclo[2.2.2]oct-7-en-2,3,5,6-tetracarboxylic acid dianhydride, etc.
[0086] In addition, examples of aliphatic tetracarboxylic acids and their derivatives represented by formula (12) include 1,2,3,4-cyclobutanetetracarboxylic acid, 1,2,4,5-cyclopentanetetracarboxylic acid, 1,2,4,5-cyclohexanetetracarboxylic acid, bicyclo[2.2.2]oct-7-en-2,3,5,6-tetracarboxylic acid, etc. and their alcohol esters. These may be used individually or in combination of two or more types. Among these, 1,2,4,5-cyclohexanetetracarboxylic acid dianhydride and 1,2,4,5-cyclohexanetetracarboxylic acid are preferably cited.
[0087] In the above manufacturing method, other tetracarboxylic acids and their derivatives may be mixed and used within a range that does not impair solvent solubility. For example, pyromellitic acid, 3,3',4,4'-biphenyltetracarboxylic acid, 2,3,3',4'-biphenyltetracarboxylic acid, 2,2-bis(3,4-dicarboxyphenyl)propane, 2,2-bis(2,3-dicarboxyphenyl)propane, 2,2-bis(3,4-dicarboxyphenyl)-1,1,1,3,3,3-hexafluoropropane, 2,2-bis(2,3-dicarboxyphenyl)-1,1,1,3,3,3-hexafluoropropane, bis(3,4-dicarboxyphenyl)sulfone, bis(3,4-dicarboxyphenyl)ether, bis(2,3-dicarboxyphenyl)ether, 3,3',4,4'-benzophenonetetracarboxylic acid, Examples include 2,2',3,3'-benzophenonetetracarboxylic acid, 4,4-(p-phenylenedioxy)diphthalic acid, 4,4-(m-phenylenedioxy)diphthalic acid, ethylenetetracarboxylic acid, 3-carboxymethyl-1,2,4-cyclopentanetricarboxylic acid, 1,1-bis(2,3-dicarboxyphenyl)ethane, bis(2,3-dicarboxyphenyl)methane, bis(3,4-dicarboxyphenyl)methane, etc., and their derivatives. It is preferable that the proportion of these other tetracarboxylic acid components be less than 50 mol% of the total tetracarboxylic acid components.
[0088] The above diamine compound is preferably an aromatic diamine compound containing 6 to 28 carbon atoms or an aliphatic diamine compound containing 2 to 28 carbon atoms. As diamine compounds, for example, p-phenylenediamine, m-phenylenediamine, 4,4'-diaminobiphenyl, 4,4'-diamino-2,2'-dimethylbiphenyl, 4,4'-diamino-3,3'-dimethylbiphenyl, 4,4'-diamino-2,2'-ditrifluoromethylbiphenyl, 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 4,4'-diaminodiphenylmethane, 4,4'-diaminobenzophenone, 4,4'-diaminodiphenylsulfone, 4,4'-diaminodiphenylsulfide, 1,4-bis(4-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)biphenyl, bis[4-(4-aminophenoxy)phenyl]sulfone, Examples include aromatic diamine compounds such as 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 2,2-bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, bis[4-(3-aminophenoxy)phenyl]sulfone, and 9,9-bis(4-aminophenyl)fluorene, as well as ethylenediamine, hexamethylenediamine, polyethylene glycol bis(3-aminopropyl)ether, polypropylene glycol bis(3-aminopropyl)ether, 1,3-bis(aminomethyl)cyclohexane, 1,4-bis(aminomethyl)cyclohexane, 4,4'-diaminodicyclohexylmethane, 3(4),8(9)-bis(aminomethyl)-tricyclo[5.2.1.02,6]decane, methaxylylenediamine, paraxylylenediamine, isophoronediamine, Examples include aliphatic diamine compounds such as norbornandiamines and siloxanediamines. These can be used individually or in combination of two or more types.Among these diamine compounds, aromatic diamine compounds preferably include 4,4'-diamino-3,3'-dimethylbiphenyl, 4,4'-diamino-2,2'-ditrifluoromethylbiphenyl, 4,4'-diaminodiphenyl ether, 4,4'-diaminodiphenylmethane, 1,4-bis(4-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)biphenyl, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, and 2,2-bis[4-(4-aminophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, and aliphatic diamine compounds preferably include 4,4'-diaminodicyclohexylmethane, 3(4),8(9)-bis(aminomethyl)-tricyclo[5.2.1.02,6]decane is preferred.
[0089] In the above manufacturing method, it is preferable to use 0.001 to 1.0 moles of a tertiary amine compound per 1 mole of an aliphatic tetracarboxylic acid component used, and more preferable to use 0.01 to 0.2 moles.
[0090] Examples of the above tertiary amine compounds include trimethylamine, triethylamine, tripropylamine, tributylamine, triethanolamine, N,N-dimethylethanolamine, N,N-diethylethanolamine, triethylenediamine, N-methylpyrrolidine, N-ethylpyrrolidine, N-methylpiperidine, N-ethylpiperidine, imidazole, pyridine, quinoline, isoquinoline, etc. Among these tertiary amine compounds, triethylamine is particularly preferred.
[0091] Examples of solvents used in the above manufacturing method include γ-butyrolactone, N,N-dimethylacetamide, N-methyl-2-pyrrolidone, N,N-dimethylformamide, dimethyl sulfoxide, hexamethylphosphoramide, tetramethylenesulfone, p-chlorophenol, m-cresol, 2-chloro-4-hydroxytoluene, etc. These may be used individually or in a mixture of two or more types. Among these, γ-butyrolactone, N,N-dimethylacetamide, and N-methyl-2-pyrrolidone are preferred, and γ-butyrolactone and N,N-dimethylacetamide are more preferred. In addition, a poor solvent of the polyimide resin may be used in combination to the extent that the polymer does not precipitate. Examples of solvents include hexane, heptane, benzene, toluene, xylene, chlorobenzene, o-dichlorobenzene, etc.
[0092] In the above manufacturing method, the amount of solvent used is preferably 1 to 50 mass% of the total weight of the aliphatic tetracarboxylic acid component and the diamine component relative to the total mass of the reaction solution, and more preferably 20 to 45 weight%.
[0093] The method of introducing the aliphatic tetracarboxylic acid component and the diamine compound component is not particularly limited, and methods such as introducing both components at once, or slowly introducing one component in a solid or solution state into a solution containing one of the components (which does not need to be completely dissolved) can be implemented. In particular, the method of introducing both components at once is advantageous in terms of productivity because it can shorten the introduction time.
[0094] In order to fully exert its catalytic effect, it is desirable to add the tertiary amine compound by raising the temperature until the target temperature is reached. In particular, it is desirable to add it simultaneously with the solvent, the aliphatic tetracarboxylic acid component, and the diamine compound.
[0095] The method of introducing the above solvent is not particularly limited, and methods such as introducing it into the reaction vessel in advance, introducing it into a reaction vessel where either or both of the aliphatic tetracarboxylic acid component or the diamine compound are present, or dissolving either the aliphatic tetracarboxylic acid component or the diamine component in advance and then introducing it into the reaction vessel can be carried out individually or in combination. In addition, the solvent described above may be added according to the purpose to the solvent-soluble polyimide resin solution in the state during the reaction, in the state remaining in the reaction vessel after the reaction, or in the state removed from the reaction vessel after the reaction.
[0096] In addition, as the polyimide resin (B) used in this embodiment, for example, a block copolymer polyimide resin may be used. Examples of block copolymer polyimide resins include the block copolymer polyimide resin described in International Publication No. WO2010-073952. Specifically, the block copolymer polyimide resin is not particularly limited as long as it is a copolymer polyimide resin having a structure in which a structure B1, in which an imide oligomer formed by a second structural unit is bonded to the end of an imide oligomer formed by a first structural unit, and a structure B2, in which an imide oligomer formed by a first structural unit is bonded to the end of an imide oligomer formed by a second structural unit, are alternately repeated. In addition, the second structural unit is different from the first structural unit. These block copolymer polyimide resins can be synthesized by a sequential polymerization reaction in which a tetracarboxylic acid dianhydride is reacted with a diamine in a polar solvent to form an imide oligomer, and then a tetracarboxylic acid dianhydride is further mixed with another diamine or a tetracarboxylic acid dianhydride is mixed with a diamine to form an imide.
[0097] The ratio of polyimide resin (B) in the first resin layer (12) is not particularly limited, but in terms of heat resistance and curability, a range of 10 parts by mass or more and 80 parts by mass or less is preferred with respect to 100 parts by mass of resin solid content of the first resin layer (12), and a range of 30 parts by mass or more and 70 parts by mass or less is particularly preferred.
[0098] The first resin layer (12) may contain only one type of polyimide resin (B) or two or more types. When two or more types are included, it is preferable that the total amount be within the above range.
[0099] <Malayimide Compound (C)>
[0100] By including a maleimide compound (C), interlayer adhesion, insulation, plating adhesion, and moisture absorption and heat resistance can be improved. As for the maleimide compound (C), any conventionally known maleimide compound can be used, provided that it is a compound having one or more maleimide groups (preferably 2 to 12, more preferably 2 to 6, even more preferably 2 to 4, even more preferably 2 or 3, and even more preferably 2) in one molecule.
[0101] Specific examples of maleimide compounds (C) include, for example, bis-maleimide compounds such as bis(4-maleimidephenyl)methane, 2,2-bis-(4-(4-maleimidephenoxy)phenyl)propane, bis(3,5-dimethyl-4-maleimidephenyl)methane, bis(3-ethyl-5-methyl-4-maleimidephenyl)methane, and bis(3,5-diethyl-4-maleimidephenyl)methane; and polyphenylmethanemaleimide. In addition, maleimide compounds (C) may be formulated in the form of a prepolymer of these compounds, or a prepolymer of these compounds and an amine compound. One or more of these maleimide compounds (C) may be used in an appropriate mixture.
[0102] Among these, bismaleimide compounds are preferred in terms of heat resistance, and among them, 2,2-bis-(4-(4-maleimidephenoxy)phenyl)propane or bis(3-ethyl-5-methyl-4-maleimidephenyl)methane are more preferred.
[0103] The ratio of the maleimide compound (C) in the first resin layer (12) is not particularly limited, but in terms of heat resistance and plating adhesion, a range of 5 parts by mass or more and 75 parts by mass or less is preferred with respect to 100 parts by mass of the resin solid content of the first resin layer (12), and a range of 5 parts by mass or more and 45 parts by mass or less is more preferred.
[0104] The first resin layer (12) may contain only one type of maleimide compound (C) or two or more types. When two or more types are included, it is preferable that the total amount be within the above range.
[0105] Other resin components
[0106] Other resin components may include, for example, liquid crystal polyester, epoxy compound, cyanate ester compound, phenol compound, benzoxazine compound, organically modified silicone compound, and a compound having a polymerizable unsaturated group. The first resin layer (12) may include one or more of these.
[0107] -Liquid crystal polyester-
[0108] Liquid crystal polyester is an aromatic polyester that exhibits liquid crystal properties upon melting. As a liquid crystal polyester, a known one can be appropriately selected and used. As a known liquid crystal polyester, for example, an aromatic polyester described in Japanese Patent Publication No. 2001-11296 can be used. Specifically, an aromatic polyester containing 90 mol% or more of the structural unit represented by the following formula (13) can be used.
[0109]
[0110] As for the aromatic polyester containing the structural unit represented by the above formula (13), for example, polyoxybenzoate, which is substantially a homopolymer of the structural unit represented by the above formula (13), can be used from the perspective of availability. As for the method of manufacturing the above aromatic polyester, a known method may be adopted. Furthermore, most aromatic polyesters containing the structural unit represented by the above formula (13) are poorly soluble or insoluble in ordinary solvents, and do not exhibit liquid crystal properties because they are poorly fused or infused. Therefore, it is preferable to use the aromatic polyester containing the structural unit represented by the above formula (13) in powder form. The above powder is obtained by crushing the resin or fiber of the aromatic polyester.
[0111] Although not specifically limited, the molecular weight of the liquid crystal polyester is usually 1,000 to 100,000, and preferably 10,000 to 50,000.
[0112] As for the liquid crystal polyester, a commercially available product can be appropriately selected and used, but for example, "Econol E101-F", a product of SUMITOMO CHEMICAL COMPANY, LIMITED, can be used. In this embodiment, when liquid crystal polyester is used in the first resin layer (12), the content is not particularly limited, but in terms of heat resistance and curability, a range of 10 to 90 parts by mass per 100 parts by mass of the resin solid content of the first resin layer (12) is preferred, and a range of 30 to 80 parts by mass is particularly preferred.
[0113] -Epoxy Compound-
[0114] As for the epoxy compound, any conventionally known epoxy compound may be used, provided that it is a compound having one or more epoxy groups (preferably 2 to 12, more preferably 2 to 6, even more preferably 2 to 4, even more preferably 2 or 3, and even more preferably 2) in one molecule. The epoxy equivalent of the epoxy compound is preferably 250 g / eq to 850 g / eq, and more preferably 250 g / eq to 450 g / eq, in order to further improve adhesion and flexibility. The epoxy equivalent can be measured by a conventional method.
[0115] Specific examples of epoxy compounds include, for instance, polyoxynaphtylene-type epoxy resin, biphenyl-aralkyl-type epoxy resin, naphthalene tetrafunctional-type epoxy resin, xylene-type epoxy resin, naphthol-aralkyl-type epoxy resin, bisphenol A-type epoxy resin, bisphenol F-type epoxy resin, bisphenol A novolak-type epoxy resin, trifunctional phenol-type epoxy resin, tetrafunctional phenol-type epoxy resin, naphthalene-type epoxy resin, biphenyl-type epoxy resin, aralkyl-novolak-type epoxy resin, alicyclic epoxy resin, polyol-type epoxy resin, glycidylamine-type epoxy resin, glycidyl ester-type epoxy resin, compounds in which double bonds such as butadiene are epoxidized, and compounds obtained by the reaction of hydroxyl group-containing silicone resins with epichlorohydrin. Among these, it is preferable to use polyoxynaphtylene-type epoxy resin, biphenyl-aralkyl-type epoxy resin, naphthalene tetrafunctional-type epoxy resin, xylene-type epoxy resin, or naphthol-aralkyl-type epoxy resin, particularly in terms of copper plating adhesion and flame retardancy. One or more of these epoxy compounds may be used in an appropriate mixture.
[0116] In the present embodiment, when an epoxy compound is used in the first resin layer (12), the content is not particularly limited, but in terms of heat resistance and curability, a range of 1 to 60 parts by mass per 100 parts by mass of resin solid content of the first resin layer (12) is preferred, and a range of 1 to 30 parts by mass is particularly preferred.
[0117] -Cyanate ester compounds-
[0118] Cyanide ester compounds have excellent properties such as chemical resistance and adhesion, and because it is possible to form a uniform roughened surface due to their excellent chemical resistance, they can be suitably used as a component of the resin layer in the present embodiment.
[0119] The cyanate ester compound is not particularly limited as long as it is a compound containing one or more cyanate groups (cyanato groups) in the molecule (preferably 2 to 12, more preferably 2 to 6, even more preferably 2 to 4, even more preferably 2 or 3, and even more preferably 2), and any compound commonly used in the field of printed circuit boards can be widely used. Specific examples of cyanate ester compounds include, for instance, at least one selected from the group consisting of an α-naphthol-aryl-type cyanate ester compound represented by formula (14), a phenol-novolak-type cyanate ester compound represented by formula (15), a biphenyl-aryl-type cyanate ester compound represented by formula (16), a naphthylene ether-type cyanate ester compound, a xylene resin-type cyanate ester compound, a trisphenol-methane-type cyanate ester compound, an adamantane-frame-type cyanate ester compound, a bisphenol-M-type cyanate ester compound, a bisphenol-A-type cyanate ester compound, and a diallyl-bisphenol-A-type cyanate ester compound. Among these, in order to further improve low absorption, it is preferable to select at least one from the group consisting of an α-naphthol-aralkyl type cyanate ester compound represented by formula (14), a phenol-novolak type cyanate ester compound represented by formula (15), a biphenyl-aralkyl type cyanate ester compound represented by formula (16), a naphthylene ether type cyanate ester compound, a xylene resin type cyanate ester compound, a bisphenol M type cyanate ester compound, a bisphenol A type cyanate ester compound, and a diallyl-bisphenol A type cyanate ester compound. These cyanate ester compounds may be prepared by known methods or commercially available products may be used.
[0120] Among these, the α-naphthol-aralkyl type cyanate ester compound represented by formula (14), the phenol-novolak type cyanate ester compound represented by formula (15), and the biphenyl-aralkyl type cyanate ester compound represented by formula (16) are preferred because they have excellent flame retardancy, high curability, and a low coefficient of thermal expansion of the cured product.
[0121]
[0122] (In Equation (14), R 1 represents a hydrogen atom or a methyl group, and n 1 represents an integer greater than or equal to 1. n 1 It is preferable that is an integer between 1 and 50.
[0123]
[0124] (In Equation (15), R 2 represents a hydrogen atom or a methyl group, and n 2 represents an integer greater than or equal to 1. n 2 It is preferable that is an integer between 1 and 50)
[0125]
[0126] (In Equation (16), R 3 represents a hydrogen atom or a methyl group, and n 3 represents an integer greater than or equal to 1. n 3 It is preferable that is an integer between 1 and 50)
[0127] In the present embodiment, when a cyanate ester compound is used in the first resin layer (12), the content is not particularly limited, but in terms of heat resistance and adhesion to copper foil, a range of 1 to 60 parts by mass per 100 parts by mass of resin solid content of the first resin layer (12) is preferred, and a range of 1 to 30 parts by mass is more preferred.
[0128] -Phenol compounds-
[0129] As for the phenol compound, any conventionally known phenol compound can be used, provided that it is a phenol compound having one or more phenolic hydroxyl groups (preferably 2 to 12, more preferably 2 to 6, even more preferably 2 to 4, even more preferably 2 or 3, and even more preferably 2) in one molecule. Specific examples of phenol compounds include, for instance, bisphenol A type phenol resin, bisphenol E type phenol resin, bisphenol F type phenol resin, bisphenol S type phenol resin, phenol novolak resin, bisphenol A novolak type phenol resin, glycidyl ester type phenol resin, aryl-kil novolak phenol resin, biphenyl-aryl-kil type phenol resin, cresol-arvolak type phenol resin, polyfunctional phenol resin, naphthol resin, naphthol novolak resin, polyfunctional naphthol resin, anthracene type phenol resin, naphthalene skeleton modified novolak type phenol resin, phenol-aryl-kil type phenol resin, naphthol-aryl-kil type phenol resin, dicyclopentadiene type phenol resin, biphenyl type phenol resin, alicyclic phenol resin, polyol type phenol resin, phosphorus-containing phenol resin, hydroxyl group-containing silicone resins, etc. These phenol compounds may be used in an appropriate mixture of one or more types.
[0130] -Benzoxazine Compound-
[0131] As for the benzoxazine compound, any compound having two or more dihydrobenzoxazine rings in one molecule is not particularly limited and generally known compounds may be used. Specific examples of benzoxazine compounds include, for instance, bisphenol A type benzoxazine BA-BXZ (product of Konishi Chemical Ind. Co., Ltd., trade name), bisphenol F type benzoxazine BF-BXZ (product of Konishi Chemical Ind. Co., Ltd., trade name), bisphenol S type benzoxazine BS-BXZ (product of Konishi Chemical Ind. Co., Ltd., trade name), etc. These benzoxazine compounds may be used individually or in a mixture of two or more types.
[0132] -Organic Modified Silicon Compounds-
[0133] Organic modified silicone compounds are not particularly limited, but specific examples include di(methylamino)polydimethylsiloxane, di(ethylamino)polydimethylsiloxane, di(propylamino)polydimethylsiloxane, di(epoxypropyl)polydimethylsiloxane, and di(epoxybutyl)polydimethylsiloxane. One or more of these organic modified silicone compounds may be used in an appropriate mixture.
[0134] -Compounds having polymerizable unsaturated groups-
[0135] As for compounds having polymerizable unsaturated groups, they are not particularly limited and generally known compounds may be used. Specific examples of compounds having polymerizable unsaturated groups include, for example, vinyl compounds such as ethylene, propylene, styrene, divinylbenzene, and divinylbiphenyl; and (meth)acrylates of monohydric or polyhydric alcohols such as methyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, polypropylene glycol di(meth)acrylate, trimethylolpropane di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, and dipentaerythritol hexa(meth)acrylate. Examples include epoxy(meth)acrylates such as bisphenol A type epoxy(meth)acrylate and bisphenol F type epoxy(meth)acrylate; and benzocyclobutene resin. One or more of these polymerizable unsaturated groups may be used in an appropriate mixture.
[0136] Inorganic Filler
[0137] The first resin layer (12) may not include an inorganic filler, but may include one. If it does include one, the content is preferably 35 volume% or less, and more preferably 31 volume% or less. This is because adding an inorganic filler improves processability, but if the content becomes excessively high, flexibility decreases, leading to cracks or reduced insulation. Additionally, the content of the inorganic filler is the content of the inorganic filler relative to the first resin layer (12) (inorganic filler / first resin layer × 100).
[0138] As for inorganic fillers, spherical fillers may be used in terms of low thermal expansion coefficient, formability, fillability, and rigidity, and are not particularly limited as long as they are spherical fillers used in the insulating layer of a printed circuit board. Examples of inorganic fillers include magnesium hydroxide; magnesium oxide; silica such as natural silica, fused silica, amorphous silica, hollow silica; molybdenum compounds such as molybdenum disulfide, molybdenum oxide, and zinc molybdate; alumina; aluminum nitride; glass; talc; titanium compounds such as titanium oxide, barium titaniumate, and strontium titaniumate; and zirconium oxide. These may be used in an appropriate mixture of one or more types.
[0139] Among them, silica is preferred as an inorganic filler due to its low thermal expansion, and specifically, spherical fused silica is preferred. Examples of commercially available spherical fused silica include SO-C1, SO-E1, YC100C, SC2500-SQ, K180SQ-C1 from ADMATECHS COMPANY LIMITED, M273 from CIK NanoTek Corporation, and SFP-20M and SFP-130MC from Denka Company Limited.
[0140] The particle size of the inorganic filler is not particularly limited, but is preferably 5 μm or less, more preferably 3 μm or less, even more preferably 2 μm or less, and even more preferably 1.0 μm or less. The particle size of the inorganic filler can be measured by the laser diffraction scattering method based on the Mie scattering theory. Preferably, the measurement sample can be one in which the inorganic filler is dispersed in water by ultrasound. As a laser diffraction scattering particle size distribution measuring device, the "MT3000 II" manufactured by Microtrac BEL Corp. can be used.
[0141] In addition, the inorganic filler may be surface-treated with a silane coupling agent, etc. As the silane coupling agent, the silane coupling agent described below may be used.
[0142] [Other ingredients]
[0143] As for other components, for example, a silane coupling agent may be included for the purpose of improving moisture absorption and heat resistance. As for the silane coupling agent, any silane coupling agent generally used for surface treatment of inorganic materials is not particularly limited. Specific examples include aminosilane-based silane coupling agents (e.g., γ-aminopropyltriethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane), epoxysilane-based silane coupling agents (e.g., γ-glycidoxypropyltrimethoxysilane), acrylsilane-based silane coupling agents (e.g., γ-acryloxypropyltrimethoxysilane), vinylsilane-based silane coupling agents (e.g., γ-methacryloxypropyltrimethoxysilane), cationic silane-based silane coupling agents (e.g., N-β-(N-vinylbenzylaminoethyl)-γ-aminopropyltrimethoxysilane hydrochloride), phenylsilane-based silane coupling agents, etc. One or more of these silane coupling agents may be used in an appropriate mixture.
[0144] In the present embodiment, the content of the silane coupling agent is not particularly limited, but for the sake of improving moisture absorption and heat resistance, a range of 0.05 to 5 parts by mass per 100 parts by mass of inorganic filler is preferred, and a range of 0.1 to 3 parts by mass is more preferred. In addition, when two or more types of silane coupling agents are used in combination, it is preferable that the total amount of these silane coupling agents satisfies the above range.
[0145] As for other ingredients, a wetting dispersant may be further included, for example, for the purpose of improving manufacturability. As for the wetting dispersant, any wetting dispersant generally used in paints, etc. is not particularly limited. Specific examples include BYK Japan KK products such as Disperbyk (registered trademark)-110, Disperbyk-111, Disperbyk-118, Disperbyk-180, Disperbyk-161, BYK (registered trademark)-W996, BYK-W9010, and BYK-W903. These wetting dispersants may be used in an appropriate mixture of one or more types.
[0146] In the present embodiment, the content of the wetting dispersant is not particularly limited, but for the sake of improved manufacturability, a range of 0.1 to 5 parts by mass per 100 parts by mass of inorganic filler is preferred, and a range of 0.5 to 3 parts by mass is more preferred. In addition, when two or more wetting dispersants are used in combination, it is preferable that the total amount of these satisfies the above range.
[0147] As for other components, a curing accelerator may be additionally included for purposes such as adjusting the curing speed. As hardening accelerators, although not particularly limited, organometallic salts containing metals such as copper, zinc, cobalt, nickel, and manganese (e.g., lead naphthenate, lead stearate, zinc naphthenate, zinc octylate, tin oleate, dibutyltin maleate, manganese naphthenate, cobalt naphthenate, nickel octylate, manganese octylate, iron acetylacetone), compounds formed by dissolving these organometallic salts in hydroxyl group-containing compounds such as phenol and bisphenol, organotin compounds (e.g., inorganic metal salts such as tin chloride, zinc chloride, and aluminum chloride; dioctyltin oxide, other alkyltins, and alkyltin oxides), imidazoles and their derivatives (e.g., 2-ethyl-4-methylimidazole, 1-benzyl-2-phenylimidazole, 2,4,5-triphenylimidazole), and tertiary Examples include amines (e.g., triethylamine, N,N-dimethylbenzylamine, N,N-dimethylaniline, N,N-dimethyltoluidine, 2-N-ethylanilineoethanol, tri-n-butylamine, pyridine, quinoline, N-methylmorpholine, triethanolamine, triethylenediamine, tetramethylbutanediamine, N-methylpiperidine, etc.), organic peroxides (e.g., benzoyl peroxide, lauroyl peroxide, acetyl peroxide, parachlorobenzoyl peroxide, di-tert-butyl-di-perphthalate), azo compounds (e.g., azobisnitrile), and phenols (e.g., phenol, xylenol, cresol, resorcinol, catechol). These curing accelerators may be used in an appropriate mixture of one or more types.
[0148] In the present embodiment, the content of the curing accelerator is not particularly limited, but in order to obtain a high glass transition temperature, a range of 0.001 to 5 parts by mass per 100 parts by mass of the resin solid content of the first resin layer (12) is preferred, and a range of 0.01 to 3 parts by mass is more preferred. In addition, when two or more types of curing accelerators are used in combination, it is preferable that the total amount of these satisfies the above range.
[0149] Other components may include, for example, various other polymer compounds and / or flame-retardant compounds. As for the polymer compounds and flame-retardant compounds, they are not particularly limited as long as they are commonly used.
[0150] Examples of polymer compounds include various thermosetting resins, thermoplastic resins, their oligomers, and elastomers. Specifically, examples include polyamideimide resin, polystyrene, polyolefin, styrene-butadiene rubber (SBR), isoprene rubber (IR), butadiene rubber (BR), acrylonitrile-butadiene rubber (NBR), polyurethane, polypropylene, (meth)acrylic oligomers, (meth)acrylic polymers, and silicone resins. Acrylonitrile-butadiene rubber or styrene-butadiene rubber is preferred in terms of compatibility.
[0151] Specific examples of flame-retardant compounds include phosphorus-containing compounds (e.g., phosphate esters, melamine phosphate, phosphorus-containing epoxy compounds), nitrogen-containing compounds (e.g., melamine, benzoguanamine), oxazine ring-containing compounds, silicone-based compounds, etc. One or more of these polymer compounds and / or flame-retardant compounds may be used in an appropriate mixture.
[0152] The first resin layer (12) may contain various other additives depending on the purpose. Specific examples of additives include ultraviolet absorbers, antioxidants, photopolymerization initiators, fluorescent whitening agents, photosensitizers, dyes, pigments, thickeners, lubricants, defoaming agents, dispersants, leveling agents, and gloss agents. These additives may be used in appropriately mixed forms of one or more types.
[0153] [Second resin layer]
[0154] The second resin layer (13) contains a thermosetting resin. The thermosetting resin is not particularly limited, but examples include epoxy compounds, cyanate ester compounds, maleimide compounds, phenol compounds, polyphenylene ether compounds, benzoxazine compounds, organically modified silicone compounds, and compounds having polymerizable unsaturated groups. As these compounds, the same ones exemplified in the first resin layer (12) may be used. The thermosetting resin may be used by appropriately mixing one or more of these types. Among them, it is preferable to include an epoxy compound and a phenol compound because excellent peel strength can be obtained, and it is even more preferable to include a maleimide compound together with the epoxy compound and the phenol compound.
[0155] In the present embodiment, when an epoxy compound is used in the second resin layer (13), the content is not particularly limited, but in terms of heat resistance and curability, a range of 10 to 80 parts by mass per 100 parts by mass of resin solid content of the second resin layer (13) is preferred, and a range of 30 to 70 parts by mass is particularly preferred.
[0156] In the present embodiment, when a phenol compound is used in the second resin layer (13), the content is not particularly limited, but in terms of heat resistance and adhesion to copper foil, a range of 10 to 80 parts by mass per 100 parts by mass of resin solid content of the second resin layer (13) is preferred, and a range of 20 to 60 parts by mass is more preferred.
[0157] In the present embodiment, when a maleimide compound is used in the second resin layer (13), the content is not particularly limited, but in terms of heat resistance and adhesion to the copper foil, a range of 10 to 80 parts by mass per 100 parts by mass of the resin solid content of the second resin layer (13) is preferred, and a range of 10 to 50 parts by mass is more preferred.
[0158] The thickness of the second resin layer (13) is not particularly limited, but from the perspective of thinning, it is preferable that it be 15 μm or less, and more preferable that it be 10 μm or less. In addition, considering the securing of insulation properties, the thickness of the second resin layer (13) is preferably 1 μm or more. The second resin layer (13) is preferably in a semi-cured state (B-Stage). The second resin layer (13) can be formed by known means, such as coating, for example.
[0159] The second resin layer (13) may additionally include at least one of an inorganic filler and other components as needed. The inorganic filler and other components may be the same as those described in the first resin layer (12), for example. The second resin layer (13) may not include an inorganic filler, but may include one, and it is preferable that the content be 35 volume% or less. This is because adding an inorganic filler improves processability, but if the content becomes excessively high, flexibility decreases and cracks are more likely to occur. In addition, the content of the inorganic filler is the content of the inorganic filler relative to the second resin layer (13) (inorganic filler / first resin layer × 100).
[0160] [Method for manufacturing copper foil with resin layer attached]
[0161] The method for manufacturing the copper foil (10) with the resin layer attached according to the present embodiment is not particularly limited. As a manufacturing method, for example, a solution (varnish) in which the composition of the first resin layer (12) is dissolved or dispersed in an organic solvent is first applied to the surface of the copper foil (11), dried under heating and / or reduced pressure, and solidified by removing the solvent to form the first resin layer (12). As described above, the first resin layer (12) may be in a semi-cured state as well as a fully cured state. After that, it is preferable to form the second resin layer (13) by applying a solution (varnish) in which the composition of the second resin layer (13) is dissolved or dispersed in an organic solvent onto the first resin layer (12), drying under heating and / or reduced pressure, and solidifying by removing the solvent. At this time, it is preferable to make the second resin layer (13) a B-stage (semi-cured state). Additionally, a protective layer, such as a plastic film, may be formed on the second resin layer (13). The protective layer is appropriately removed during the fabrication of the laminate described later.
[0162] The drying conditions are not particularly limited, but the first resin layer (12) or the second resin layer (13) is dried such that the organic solvent is usually 10 parts by mass or less, preferably 5 parts by mass or less, per 100 parts by mass. The conditions for achieving drying vary depending on the amount of organic solvent in the varnish, but for example, in the case of a varnish containing 30 to 60 parts by mass of organic solvent per 100 parts by mass of varnish, it is preferable to dry it for about 3 to 10 minutes under heating conditions of 50°C to 200°C.
[0163] As for the organic solvent, it is not particularly limited as long as it can suitably dissolve or disperse each component and also obtain the effect of the first resin layer (12) or the second resin layer (13). Specific examples of organic solvents include alcohols (e.g., methanol, ethanol, and propanol), ketones (e.g., acetone, methyl ethyl ketone, and methyl isobutyl ketone), amides (e.g., dimethylacetamide and dimethylformamide), aromatic hydrocarbons (e.g., toluene and xylene), N-methyl-2-pyrrolidone, or γ-butyrolactone. One or more of these organic solvents may be used in a suitable mixture.
[0164] Although there are no particular limitations on the application method, known application methods such as bar coater application, air knife application, gravure application, reverse gravure application, micro gravure application, micro reverse gravure coater application, die coater application, dip application, spin coat application, and spray application may be used.
[0165] [Laminated body and method of manufacturing the same]
[0166] A laminate using the copper foil (10) with a resin layer attached according to the present embodiment (hereinafter simply referred to as "the laminate of the present embodiment") can be used, for example, as a build-up material for a printed circuit board or a substrate for mounting semiconductor devices, or for manufacturing a coreless substrate.
[0167] The laminate of the present embodiment may be configured as a laminate having a build-up layer formed by alternately laminating a conductor layer and an insulating layer formed using a copper foil (10) with a resin layer attached. Here, the "insulating layer formed using a copper foil (10) with a resin layer attached" may be configured by laminating, for example, a second resin layer (13) of the copper foil (10) with a resin layer attached to a substrate on which a conductor layer is formed. In addition, when the insulating layer is formed using three or more copper foils (10) with resin layers attached, the copper foil (11) may be removed as necessary, and the insulating layer may be formed by laminating the first resin layer (12) and the second resin layer (13). Furthermore, the conductor layer may be formed by the copper foil (11) of the copper foil (10) with a resin layer attached, or by laminating another conductor (copper foil, etc.), such as the copper foil of a copper foil laminate, separately. FIG. 2 shows an example of the laminate (20) of the present embodiment. This laminate (20) is formed by laminating a copper foil (10) with a resin layer attached to it on a substrate (22) on which a conductor layer (21) is formed, so that a second resin layer (13) is in contact with it, and an insulating layer (23) is formed by the first resin layer (12) and the second resin layer (13).
[0168] In the case where the laminate of the present embodiment has a build-up layer, for example, the build-up layer may have a plurality of conductor layers and an insulating layer, and the conductor layers may be configured to be disposed between each insulating layer and on the surface of the outermost layer of the build-up layer. At this time, the number of insulating layers is not particularly limited, but may be, for example, three layers or four layers.
[0169] In addition, a coreless substrate can be manufactured using the laminate of the present embodiment. As for the coreless substrate, for example, a coreless substrate with two or more layers can be cited, and for example, a three-layer coreless substrate can be cited. The configuration of the coreless substrate will be described later.
[0170] [Printed Wiring Board]
[0171] The laminate of the present embodiment can be used as a printed circuit board. Here, the printed circuit board can be obtained by using a laminate in which the copper foil (10) with the resin layer attached to it of the present embodiment is used as a build-up material with respect to a metal foil laminate in which an insulating resin layer called a core substrate is fully cured. By using the copper foil (10) with the resin layer attached to it of the present embodiment (laminated), it is possible to manufacture a thin printed circuit board without using, for example, a thick support substrate (carrier substrate).
[0172] A conductive circuit is formed on the surface of the metal foil laminate by a conductive layer obtained by the metal foil of a commonly used metal foil laminate and / or by plating after peeling off the metal foil. In addition, the substrate of the metal foil laminate is not particularly limited, but is mainly a glass epoxy substrate, a metal substrate, a polyester substrate, a polyimide substrate, a BT (Bismaleimide Triazine) resin substrate, and a thermosetting polyphenylene ether substrate.
[0173] The build-up in this embodiment involves laminating a first resin layer (12) and, if necessary, a second resin layer (13) of a copper foil (10) with a resin layer attached to the metal foil and / or conductor layer on the surface of a metal foil laminate. When manufacturing a printed circuit board or a substrate for mounting semiconductor devices, even if plating treatment is performed after etching the copper foil (11), the first resin layer (12) has excellent plating adhesion, so the plating adhesion is improved.
[0174] In the manufacture of printed circuit boards, holes such as via holes and / or through holes are drilled to electrically connect each conductor layer as needed. Hole drilling is typically performed using a mechanical drill, a carbon dioxide laser, a UV laser, and a YAG laser.
[0175] When hole processing is performed, a shaping treatment including desmearing is subsequently carried out. The shaping treatment usually consists of a swelling process, a surface shaping and smear dissolution process, and a neutralization process. The swelling process is carried out by swelling the surface of the insulating resin layer using a swelling agent. As for the swelling agent, it is not particularly limited as long as it can swell the surface of the insulating resin layer to the extent that oxidative decomposition is promoted in the subsequent surface shaping and smear dissolution process, while improving the wettability of the surface of the insulating resin layer. Examples include alkaline solutions and surfactant solutions. The surface shaping and smear dissolution process is carried out using an oxidizing agent. Examples of oxidizing agents include alkaline permanganate solutions, and specific examples preferably include aqueous potassium permanganate solutions and aqueous sodium permanganate solutions. This oxidizing agent treatment is called wet desmearing, and in addition to the wet desmearing, other known oxidizing treatments such as dry desmearing by plasma treatment or UV treatment, mechanical polishing by buffing, and sandblasting may be appropriately combined. The neutralization process is to neutralize the oxidizing agent used in the preceding process with a reducing agent. As a reducing agent, amine-based reducing agents may be used, and specific examples preferably include acidic aqueous solutions such as an aqueous solution of hydroxylamine sulfate, an aqueous solution of ethylenediamine tetraacetic acid, and an aqueous solution of nitrilosaacetic acid.
[0176] In the present embodiment, it is preferable to perform metal plating treatment to electrically connect each conductor layer after forming via holes and / or through holes or after desmearing the inside of the via holes and / or through holes. The method of metal plating treatment is not particularly limited, and a metal plating treatment method used in the manufacture of ordinary multilayer printed circuit boards can be appropriately used. The method of metal plating treatment and the type of chemical solution used for plating are not particularly limited, and a metal plating treatment method and chemical solution used in the manufacture of ordinary multilayer printed circuit boards can be appropriately used. The chemical solution used for metal plating treatment may be a commercially available product. The method of metal plating treatment is not particularly limited and may include, for example, treatment with a degreasing solution, treatment with a soft etching solution, acid cleaning, treatment with a pre-dip solution, treatment with a catalyst solution, treatment with an accelerator solution, treatment with a chemical copper solution, and treatment by acid cleaning and immersion in copper sulfate solution and passing an electric current.
[0177] In addition, when a semi-cured copper foil (10) with a resin layer attached is used for build-up, a printed circuit board can be obtained by performing heat treatment or the like on the first resin layer (12) or the second resin layer (13) in a semi-cured state to fully cure it. In this embodiment, another copper foil (10) with a resin layer attached may be further laminated onto the obtained printed circuit board.
[0178] As for the lamination method in the build-up method, there are no particular limitations, but a vacuum pressure type laminator may be suitably used. In this case, the copper foil (10) with the resin layer attached may be laminated with an elastic body such as rubber in between. As for the lamination conditions, there are no particular limitations as long as they are conditions used for the lamination of ordinary printed circuit boards, but for example, they are carried out at a temperature of 70°C to 140°C, a contact pressure in the range of 1 kgf / ㎠ to 11 kgf / ㎠, and a reduced pressure atmosphere of 20 hPa or less. After the lamination process, the laminated adhesive film may be smoothed using a heat press with a metal plate. The lamination process and the smoothing process can be carried out continuously using a commercially available vacuum pressure type laminator. A heat curing process may be provided after the lamination process or after the smoothing process. By using a thermal curing process, the first resin layer (12) and the second resin layer (13) can be completely cured. The thermal curing conditions vary depending on the type of components included in the first resin layer (12) and the second resin layer (13), but typically the curing temperature is 100°C to 300°C, the pressure is 0.1 kgf / ㎠ to 100 kgf / ㎠ (about 9.8 kPa to about 9.8 MPa), and the curing time is 30 seconds to 5 hours.
[0179] Examples of methods for forming a circuit pattern on one or both sides of a printed circuit board in this embodiment include the semi-additive method, the full-additive method, and the subtractive method. Among these, the semi-additive method is preferred in that it forms a fine wiring pattern.
[0180] An example of a method for forming a circuit pattern using the semi-additive method is a method in which electroplating is selectively performed using a plating resist (pattern plating), and subsequently, the plating resist is peeled off and the entire area is etched to form a wiring pattern. In forming a circuit pattern by the semi-additive method, electroless plating and electroplating are performed in combination; in this case, it is preferable to perform drying after electroless plating and after electroplating, respectively. Drying after electroless plating is not particularly limited, but for example, it is preferable to perform it at 80°C to 180°C for 10 to 120 minutes, and drying after electroplating is not particularly limited, but for example, it is preferable to perform it at 130°C to 220°C for 10 to 120 minutes. Copper plating is preferred as the plating method.
[0181] An example of a method for forming a circuit pattern using the subtractive method is a method of forming a wiring pattern by selectively removing a conductor layer using an etching resist. Specifically, for example, it can be carried out as follows. A dry film resist (product of Hitachi Chemical Company, Ltd., RD-1225 (trade name)) is laminated onto the entire surface of a copper foil at a temperature of 110±10℃ and a pressure of 0.50±0.02MPa. Subsequently, masking is performed by exposing the film along the circuit pattern. Afterward, the dry film resist is developed with a 1% sodium carbonate aqueous solution, and finally, the dry film resist is peeled off with an amine-based resist stripping solution. Accordingly, a circuit pattern can be formed on the copper foil.
[0182] In this embodiment, an insulating resin layer and / or a conductor layer may be further laminated onto the printed circuit board to obtain a multilayer printed circuit board. A circuit board may be provided in the inner layer of the multilayer printed circuit board. The copper foil (10) attached to the resin layer constitutes one of the insulating resin layer and the conductor layer of the multilayer printed circuit board.
[0183] The lamination method is not particularly limited, and methods generally used for lamination molding of ordinary printed circuit boards may be used. Examples of lamination methods include multi-stage presses, multi-stage vacuum presses, laminators, vacuum laminators, and autoclave molding machines. The temperature during lamination is not particularly limited, but for example, 100°C to 300°C; the pressure is not particularly limited, but for example, 0.1 kgf / ㎠ to 100 kgf / ㎠ (approx. 9.8 kPa to approx. 9.8 MPa); and the heating time is not particularly limited, but is appropriately selected and carried out within the range of, for example, 30 seconds to 5 hours. Additionally, if necessary, post-curing may be performed in the temperature range of, for example, 150°C to 300°C to adjust the degree of curing.
[0184] [Substrate for mounting semiconductor devices]
[0185] As described above, the laminate of the present embodiment can be used as a substrate for mounting semiconductor devices. The substrate for mounting semiconductor devices is manufactured, for example, by laminating a copper foil (10) with a resin layer attached to a metal foil laminate and masking and patterning the copper foil on the surface or one side of the obtained laminate. The masking and patterning may use known masking and patterning methods used in the manufacture of printed circuit boards and are not particularly limited, but it is preferable to form a circuit pattern by the above-mentioned subtractive method. The circuit pattern may be formed only on one side of the laminate or may be formed on both sides.
[0186] [Multilayer Coreless Board (Multilayer Printed Circuit Board)]
[0187] The laminate of the present embodiment may be a coreless substrate as described above. As an example of the coreless substrate, a multilayer coreless substrate may be cited.
[0188] A multilayer coreless substrate may be configured such that, for example, a plurality of insulating layers comprising a first insulating layer and one or more second insulating layers laminated on one side of the first insulating layer, a first conductor layer disposed between each of the plurality of insulating layers, and a plurality of conductor layers comprising a second conductor layer disposed on the surface of the outermost layer of the plurality of insulating layers, and the first insulating layer and the second insulating layer each have a cured product of the first resin layer (12) and the second resin layer (13) of the resin layer attached copper foil (10). A specific example of a multilayer coreless substrate will be described using FIG. 3. FIG. 3 is a schematic diagram showing an example of a multilayer coreless substrate in the present embodiment. The multilayer coreless substrate (100) shown in FIG. 3 comprises a first insulating layer (111) and two second insulating layers (112) stacked in the direction of the first insulating layer (111) (in FIG. 3, the direction of the upper surface), and the first insulating layer (111) and the two second insulating layers (112) are each formed using the first resin layer (12) and the second resin layer (13) of a copper foil (10) with a resin layer attached. In addition, the multilayer coreless substrate (100) shown in FIG. 3 comprises a plurality of conductor layers, each consisting of a first conductor layer (113) disposed between each of the plurality of insulating layers (first insulating layer (111) and second insulating layer (112)) and a second conductor layer (114) disposed on the outermost layer of the plurality of insulating layers (first insulating layer (111) and second insulating layer (112)).
[0189] As such, according to the present embodiment, a copper foil with a resin layer attached having excellent insulation, plating adhesion, and moisture absorption and heat resistance, and a laminate using the same can be obtained.
[0190] (Example)
[0191] The present invention will be described in more detail below using examples and comparative examples, but the present invention is not limited by these examples.
[0192] (Examples 1–7)
[0193] A composition of the first resin layer (12) was obtained by combining 15.0 parts by mass of a terminally styrene polyphenylene ether compound (product name: OPE-2St2200, product of Mitsubishi Gas Chemical Co., Ltd.), 49.9 parts by mass of a polyimide resin (product name: Neopulim (registered trademark) S100, product of Mitsubishi Gas Chemical Co., Ltd.), 34.9 parts by mass of 2,2-bis-(4-(4-maleimidephenoxy)phenyl)propane (product name: BMI-80, product of K·I Chemical Industry Co., Ltd.), and 0.2 parts by mass of 2,4,5-triphenylimidazole (product of Tokyo Chemical Industry Co., Ltd.). Next, the composition of the first resin layer (12) was diluted with N-methyl-2-pyrrolidone (hereinafter referred to as “NMP”) to obtain varnish A. The obtained varnish A was applied to the matte side of the surface of a copper foil (11) (product name: 3EC-M2S-VLP, manufactured by Mitsui Metal Mining Co., Ltd.) with a thickness of 12 μm using a bar coater. At that time, the matte side of the copper foil (11) was set as the surface, and the 10-point average roughness Rz of the surface was set to 1.7 μm for Examples 1 to 5, 0.3 μm for Example 6, and 4.5 μm for Example 7. After that, the coating film was heated and dried at 180°C for 10 minutes to form the first resin layer (12) on the copper foil (11).
[0194] In addition, 35.8 parts by mass of biphenyl-aralkyl type phenolic resin (Product name: KAYAHARD GPH-103, hydroxyl equivalent: 230 g / eq, manufactured by Nippon Kayaku Co., Ltd.), 17.9 parts by mass of bis(3-ethyl-5-methyl-4-maleimidediphenyl)methane (Product name: BMI-70, manufactured by K.I. Chemical Co., Ltd.), 7.0 parts by mass of naphthalene-aralkyl type epoxy resin (Product name: HP-9900-75M, epoxy equivalent: 274 g / eq, manufactured by DIC Corporation), and 38.8 parts by mass of biphenyl-aralkyl type epoxy resin (Product name: NC-3000-FH-75M, manufactured by Nippon Kayaku Co., Ltd., epoxy equivalent: 320 g / eq). 0.5 parts by mass of 2,4,5-triphenylimidazole (product of Tokyo Kasei Kogyo Co., Ltd.) was mixed to obtain the composition of the second resin layer (13). Next, the composition of the second resin layer (13) was diluted with methyl ethyl ketone to obtain varnish B. The obtained varnish B was applied onto the first resin layer (12) obtained by the above method using a bar coater. After that, the coating film was heated and dried at 150°C for 10 minutes to obtain a copper foil (10) with a resin layer attached, having the first resin layer (12) and the second resin layer (13).
[0195] The thickness of the first resin layer (12) and the thickness of the second resin layer (13) were varied as follows in each embodiment. In Example 1, the thickness of the first resin layer (12) is 1.5 μm and the thickness of the second resin layer (13) is 2.5 μm; in Example 2, the thickness of the first resin layer (12) is 2.5 μm and the thickness of the second resin layer (13) is 2.5 μm; in Example 3, the thickness of the first resin layer (12) is 5.0 μm and the thickness of the second resin layer (13) is 2.5 μm; in Example 4, the thickness of the first resin layer (12) is 2.5 μm and the thickness of the second resin layer (13) is 1.5 μm; in Example 5, the thickness of the first resin layer (12) is 2.5 μm and the thickness of the second resin layer (13) is 10 μm; in Example 6, the thickness of the first resin layer (12) is 2.5 μm and the thickness of the second resin layer (13) is 2.5 μm; and in Example 7, the first resin layer (12) The thickness is 2.5㎛, and the thickness of the second resin layer (13) is 5.0㎛.
[0196] (Example 8)
[0197] Except for changing the composition of the first resin layer (12), the other parts were made the same as in Example 2, and the first resin layer (12) was formed on the surface of the copper foil (11), and the second resin layer (13) was formed on the first resin layer (12). The composition of the first resin layer (12) was obtained by combining (mixing) 18.0 parts by mass of a terminally styrene polyphenylene ether compound (product name: OPE-2St2200, manufactured by Mitsubishi Gas Chemical Co., Ltd.), 49.9 parts by mass of a polyimide resin (product name: Neopulim (registered trademark) S100, manufactured by Mitsubishi Gas Chemical Co., Ltd.), 31.9 parts by mass of 2,2-bis-(4-(4-maleimidephenoxy)phenyl)propane (product name: BMI-80, manufactured by K.I. Chemical Co., Ltd.), and 0.2 parts by mass of 2,4,5-triphenylimidazole (manufactured by Tokyo Chemical Industry Co., Ltd.).
[0198] (Example 9)
[0199] Except for changing the composition of the first resin layer (12), the other parts were made the same as in Example 2, and the first resin layer (12) was formed on the surface of the copper foil (11), and the second resin layer (13) was formed on the first resin layer (12). The composition of the first resin layer (12) was obtained by combining (mixing) 10.0 parts by mass of a terminally styrene polyphenylene ether compound (product name: OPE-2St2200, manufactured by Mitsubishi Gas Chemical Co., Ltd.), 51.9 parts by mass of a polyimide resin (product name: Neopulim (registered trademark) S100, manufactured by Mitsubishi Gas Chemical Co., Ltd.), 37.9 parts by mass of 2,2-bis-(4-(4-maleimidephenoxy)phenyl)propane (product name: BMI-80, manufactured by K.I. Chemical Co., Ltd.), and 0.2 parts by mass of 2,4,5-triphenylimidazole (manufactured by Tokyo Chemical Industry Co., Ltd.).
[0200] (Example 10)
[0201] Except for changing the composition of the first resin layer (12), the other parts were the same as in Example 2, and the first resin layer (12) was formed on the surface of the copper foil (11). The composition of the first resin layer (12) was obtained by combining (mixing) 15.0 parts by mass of a terminally styrene polyphenylene ether compound (product name: OPE-2St2200, manufactured by Mitsubishi Gas Chemical Co., Ltd.), 49.9 parts by mass of a polyimide resin (product name: Neopulim (registered trademark) S100, manufactured by Mitsubishi Gas Chemical Co., Ltd.), 34.9 parts by mass of 2,2-bis-(4-(4-maleimidephenoxy)phenyl)propane (product name: BMI-80, manufactured by K.I. Chemical Co., Ltd.), 0.2 parts by mass of 2,4,5-triphenylimidazole (manufactured by Tokyo Chemical Industry Co., Ltd.), and 79.8 parts by mass of silica (product name: K180SQ-C1, average particle size 0.18 μm, manufactured by Admatex Co., Ltd.) as an inorganic filler. The content of the inorganic filler in the first resin layer (12) (inorganic filler / first resin layer × 100) is 30.3 volume%.
[0202] In addition, the second resin layer (13) was formed on the first resin layer (12) in the same manner as in Example 2, except that the composition of the second resin layer (13) was changed. The composition of the second resin layer (13) comprises 35.8 parts by mass of biphenyl-aralkyl type phenolic resin (product name: KAYAHARD GPH-103, hydroxyl group equivalent: 230 g / eq, manufactured by Nippon Kayaku Co., Ltd.), 17.9 parts by mass of bis(3-ethyl-5-methyl-4-maleimidediphenyl)methane (product name: BMI-70, manufactured by K.I. Chemical Co., Ltd.), 7.0 parts by mass of naphthalene-aralkyl type epoxy resin (product name: HP-9900-75M, epoxy equivalent: 274 g / eq, manufactured by DIC Co., Ltd.), and 38.8 parts by mass of biphenyl-aralkyl type epoxy resin (product name: NC-3000-FH-75M, manufactured by Nippon Kayaku Co., Ltd., epoxy equivalent: 320 g / eq). It was obtained by combining 0.5 parts by mass of 2,4,5-triphenylimidazole (product of Tokyo Kasei Kogyo Co., Ltd.) and 99.5 parts by mass of slurry silica (product name: M273, average particle size 0.1 μm, product of CIK Nanotech Co., Ltd.) as an inorganic filler. The content of the inorganic filler in the second resin layer (13) (inorganic filler / second resin layer × 100) is 35.2 volume%.
[0203] (Example 11)
[0204] Except for changing the composition of the first resin layer (12), the other parts were made the same as in Example 2, and the first resin layer (12) was formed on the surface of the copper foil (11), and the second resin layer (13) was formed on the first resin layer (12). The composition of the first resin layer (12) was obtained by combining (mixing) 10.0 parts by mass of a terminally styrene polyphenylene ether compound (product name: OPE-2St2200, manufactured by Mitsubishi Gas Chemical Co., Ltd.), 49.9 parts by mass of a polyimide resin (product name: Neopulim (registered trademark) S100, manufactured by Mitsubishi Gas Chemical Co., Ltd.), 39.9 parts by mass of 2,2-bis-(4-(4-maleimidephenoxy)phenyl)propane (product name: BMI-80, manufactured by K.I. Chemical Co., Ltd.), and 0.2 parts by mass of 2,4,5-triphenylimidazole (manufactured by Tokyo Chemical Industry Co., Ltd.).
[0205] (Example 12)
[0206] Except for changing the composition of the first resin layer (12), the other parts were made the same as in Example 2, and the first resin layer (12) was formed on the surface of the copper foil (11), and the second resin layer (13) was formed on the first resin layer (12). The composition of the first resin layer (12) was obtained by combining (mixing) 7.0 parts by mass of a terminally styrene polyphenylene ether compound (product name: OPE-2St2200, manufactured by Mitsubishi Gas Chemical Co., Ltd.), 49.9 parts by mass of a polyimide resin (product name: Neopulim (registered trademark) S100, manufactured by Mitsubishi Gas Chemical Co., Ltd.), 42.9 parts by mass of 2,2-bis-(4-(4-maleimidephenoxy)phenyl)propane (product name: BMI-80, manufactured by K.I. Chemical Co., Ltd.), and 0.2 parts by mass of 2,4,5-triphenylimidazole (manufactured by Tokyo Chemical Industry Co., Ltd.).
[0207] (Example 13)
[0208] Except for changing the composition of the first resin layer (12), the other parts were made the same as in Example 2, and the first resin layer (12) was formed on the surface of the copper foil (11), and the second resin layer (13) was formed on the first resin layer (12). The composition of the first resin layer (12) was obtained by combining (mixing) 3.0 parts by mass of a terminally styrene polyphenylene ether compound (product name: OPE-2St2200, manufactured by Mitsubishi Gas Chemical Co., Ltd.), 49.9 parts by mass of a polyimide resin (product name: Neopulim (registered trademark) S100, manufactured by Mitsubishi Gas Chemical Co., Ltd.), 46.9 parts by mass of 2,2-bis-(4-(4-maleimidephenoxy)phenyl)propane (product name: BMI-80, manufactured by K.I. Chemical Co., Ltd.), and 0.2 parts by mass of 2,4,5-triphenylimidazole (manufactured by Tokyo Chemical Industry Co., Ltd.).
[0209] (Comparative Example 1)
[0210] Except for changing the composition of the first resin layer (12), the other parts were made the same as in Example 2, and the first resin layer (12) was formed on the surface of the copper foil (11), and the second resin layer (13) was formed on the first resin layer (12). The composition of the first resin layer (12) was obtained by mixing 50.0 parts by mass of a terminally styrene polyphenylene ether compound (product name: OPE-2St2200, manufactured by Mitsubishi Gas Chemical Co., Ltd.) and 50.0 parts by mass of a polyimide resin (product name: Neopulim (registered trademark) S100, manufactured by Mitsubishi Gas Chemical Co., Ltd.).
[0211] (Comparative Example 2)
[0212] Except for changing the composition of the first resin layer (12), the other parts were made the same as in Example 2, and the first resin layer (12) was formed on the surface of the copper foil (11), and the second resin layer (13) was formed on the first resin layer (12). The composition of the first resin layer (12) was obtained by mixing 30.0 parts by mass of a terminally styrene polyphenylene ether compound (product name: OPE-2St2200, manufactured by Mitsubishi Gas Chemical Co., Ltd.) and 70.0 parts by mass of a polyimide resin (product name: Neopulim (registered trademark) S100, manufactured by Mitsubishi Gas Chemical Co., Ltd.).
[0213] (Comparative Example 3)
[0214] Except for changing the composition of the first resin layer (12), the other parts were made the same as in Example 2, and the first resin layer (12) was formed on the surface of the copper foil (11), and the second resin layer (13) was formed on the first resin layer (12). The composition of the first resin layer (12) was obtained by mixing 15.0 parts by mass of a terminally styrene polyphenylene ether compound (product name: OPE-2St2200, manufactured by Mitsubishi Gas Chemical Co., Ltd.), 50.0 parts by mass of a polyimide resin (product name: Neopulim (registered trademark) S100, manufactured by Mitsubishi Gas Chemical Co., Ltd.), and 35.0 parts by mass of an epoxy compound (product name: LCE-2615, manufactured by Nippon Kayaku Co., Ltd.).
[0215] (Comparative Example 4)
[0216] Except for changing the composition of the first resin layer (12), the other parts were made the same as in Example 2, and the first resin layer (12) was formed on the surface of the copper foil (11), and the second resin layer (13) was formed on the first resin layer (12). The composition of the first resin layer (12) was obtained by mixing 50.0 parts by mass of polyimide resin (product name: Neopulim (registered trademark) S100, manufactured by Mitsubishi Gas Chemical Co., Ltd.) and 50.0 parts by mass of 2,2-bis-(4-(4-maleimidephenoxy)phenyl)propane (product name: BMI-80, manufactured by K.I. Chemical Co., Ltd.).
[0217] (Comparative Example 5)
[0218] Except for setting the 10-point average roughness Rz of the surface of the copper foil (11) to 10.5 μm, the other details were the same as in Example 7, and a first resin layer (12) was formed on the surface of the copper foil (11), and a second resin layer (13) was formed on the first resin layer (12).
[0219] (Characteristics Assessment)
[0220] The characteristics of each example and each comparative example were measured by the following method.
[0221] (Evaluation of insulation performance)
[0222] In a copper clad laminate (HL832NS (product name) T / T 0.2mmt, manufactured by Mitsubishi Gas Chemical Co., Ltd.), the copper foil surfaces on both sides were etched to a depth of about 0.5㎛ to 1㎛ (inner layer harmonization treatment, CZ8101 (product name), manufactured by MEC COMPANY LTD.), and on both sides, the copper foil (10) with a resin layer attached according to each example and each comparative example was arranged so that the second resin layer (13) was on the inside, and a copper clad laminate was obtained by performing lamination molding (thermal curing) at a pressure of 30kgf / ㎠ and a temperature of 220℃ for 120 minutes. Next, an outer layer circuit for insulation evaluation was fabricated on the obtained copper clad laminate by the subtractive method, and an insulation evaluation substrate was obtained.
[0223] For the obtained substrate for insulation evaluation, the resistance value was measured over 300 hours in a HAST test bath (130℃, 85%RH, 5.0V), and then the resistance value was measured after removal from the HAST test bath. As a result, there were no short circuits in the HAST test bath, and the resistance value after removal from the HAST test bath was 1×10⁻⁶ 8 Cases where it is Ω or higher are evaluated as good as ○, and other cases are evaluated as ×.
[0224] (Evaluation of plating adhesion)
[0225] For the copper foil (10) with a resin layer attached obtained in each example and each comparative example, after etching the copper foil (10), electroless plating and electrolytic copper plating were performed to form a plating layer with a thickness of 20 μm, thereby obtaining a test specimen. The peel strength was measured using this test specimen. For the peel strength, the lower layer of the test specimen was fixed to a plate, and the end of the plating layer was pulled perpendicularly to the direction of the fixed plate, and the load value required for peeling was set as the adhesion strength of the interface between the upper layer and the lower layer. A peel strength of 0.5 kN / m or more was judged to be satisfactory.
[0226] (Evaluation of moisture absorption and heat resistance)
[0227] In a copper clad laminate (HL832NS (product name) T / T 0.2mmt, manufactured by Mitsubishi Gas Chemical Co., Ltd.), the copper foil surfaces on both sides were etched to a depth of 0.5㎛ to 1㎛ (inner layer shaping treatment, CZ8101 (product name), manufactured by Mekku Co., Ltd.), and on both sides, the copper foil (10) with a resin layer attached according to each example and each comparative example was arranged so that the second resin layer (13) was on the inside, and a copper clad laminate was obtained by performing lamination molding (thermal curing) at a pressure of 30kgf / ㎠ and a temperature of 220℃ for 120 minutes. Next, the obtained copper clad laminate was cut to a size of 50mm × 50mm to obtain a test specimen for measurement. The heat resistance of the obtained test specimen was evaluated by leaving it in a constant temperature bath at 120℃ for 3 hours as a pretreatment, and then immersing it in a solder bath at 260℃ for 30 seconds. After 30 seconds, the occurrence of delamination was checked between (1) the copper foil on the surface of the copper clad laminate and the layer containing the cured product of the first resin layer (12) and the second resin layer (13), and (2) the layer containing the cured product of the first resin layer (12) and the second resin layer (13) and the layer containing the cured product of the resin composition in the copper clad laminate (HL832NS (product name) T / T 0.2mmt, Mitsubishi Gas Chemical Co., Ltd. product). In (1) and (2), if no delamination occurred in either case, it was marked as ○, and if delamination occurred in at least one case, it was marked as ×.
[0228] The conditions and evaluation results of each example and each comparative example are shown in Tables 1 and 2.
[0229]
[0230]
[0231] As shown in Tables 1 and 2, good results regarding insulation, plating adhesion, and moisture absorption / heat resistance were obtained according to Examples 1 to 13. In contrast, good results were not obtained in Comparative Examples 1 to 5. That is, it was found that excellent insulation, plating adhesion, and moisture absorption / heat resistance could be obtained by including a polyphenylene ether compound (A), a polyimide resin (B), and a maleimide compound (C) in the first resin layer (12), and making the 10-point average roughness Rz of the surface of the copper foil (11) 0.3 μm or more and 10 μm or less. Explanation of the symbols
[0232] 10: Copper foil with resin layer attached 11 : Copper foil 12: First resin layer 13 : Second resin layer 20 : Laminate 21 : Conductor layer 22 : Substrate 23: Insulating layer 100 : Multilayer coreless substrate 111 : First insulating layer 112 : Second insulating layer 113 : First conductor layer 114 : Second conductor layer
Claims
Claim 1 A copper foil having a copper foil and a first resin layer laminated on the surface of the copper foil, wherein the first resin layer is 3 parts by mass or more and less than 20 parts by mass per 100 parts by mass of resin solids Polyphenylene ether compound (A), 10 parts by mass or more and 80 parts by mass or less Polyimide resin (B) and 5 parts by mass or more and 75 parts by mass or less It includes a maleimide compound (C), and the 10-point average roughness Rz of the surface of the copper foil is 0.3㎛ or more and 10㎛ or less. And, A second resin layer comprising a thermosetting resin is formed on the first resin layer, and The second resin layer comprises at least one selected from the group consisting of epoxy compounds, cyanate ester compounds, maleimide compounds, phenol compounds, polyphenylene ether compounds, benzoxazine compounds, organically modified silicone compounds, and compounds having polymerizable unsaturated groups, and The above second resin layer and the above first resin layer are composed of at least one different component and physical property. Copper foil with a resin layer attached, characterized by the following: Claim 2 delete Claim 3 delete Claim 4 In claim 1, the first resin layer is a copper foil attached to a resin layer that does not contain an inorganic filler or contains an inorganic filler in an amount of 35 volume% or less. Claim 5 In claim 4, the inorganic filler is a copper foil with a resin layer attached, containing at least one selected from magnesium hydroxide, magnesium oxide, silica, molybdenum compound, alumina, aluminum nitride, glass, talc, titanium compound, and zirconium oxide. Claim 6 A copper foil with a resin layer attached, wherein the thickness of the first resin layer is 1.5㎛ or more and 5㎛ or less in the first claim. Claim 7 delete Claim 8 Paragraph 1 In this case, the second resin layer does not contain an inorganic filler, or the copper foil attached to the resin layer contains an inorganic filler in an amount of 36 volume% or less. Claim 9 In claim 8, the inorganic filler is a copper foil with a resin layer attached, containing at least one selected from magnesium hydroxide, magnesium oxide, silica, molybdenum compound, alumina, aluminum nitride, glass, talc, titanium compound, and zirconium oxide. Claim 10 Paragraph 1 In the above, the thickness of the second resin layer is 1 μm or more and 15 μm or less, and the copper foil attached to the resin layer. Claim 11 A laminate having a conductor layer and a build-up layer formed using a copper foil with a resin layer attached according to claim 1.
Citation Information
Patent Citations
Metallic foil with resin, laminated plate, printed wiring board and multilayer printed wiring board
JP2018001632A
Copper foil with resin
WO2010073952A1
Resin composition, cured object obtained from resin composition, prepreg, laminate, resin film, multilayered printed wiring board, multilayered printed wiring board for millimeter-wave radar, and poly(phenylene ether) derivative
WO2020095422A1
